Effects of cigarette smoke condensate on the production and characterization of exopolysaccharides by Bifidobacterium - Hu,Jinqiang (2015)
The aim of the study was to investigate the effect of cigarette smoke on the production and characterization of exopolysaccharides (EPSs) produced by Bifidobacterium. Cigarettes of Shanhua brand (nicotine: 1.1 mg, tar: 11 mg) were utilized to prepare a cigarette smoke condensate (CSC). The standard strain of Bifidobacterium animalis was cultured in MRS media under anaerobic addition of CSC. The results showed that CSC significantly decreased the growth of B. animalis as well as EPSs and acetic acid production. Furthermore, two EPSs fractions (Fr-I and Fr-II) were isolated and purified for chemical and molecular determination. By comparison with control, CSC was found to be of great impact on EPSs carbohydrate composition. The molecular weight mass of Fr-I changed from 3.33×105 g/mol (without CSC) to 2.99×105 (with CSC). In conclusion, in vitro studies revealed that CSC was directly able to affect the production of metabolites for B. animalis, which could be an essential factor in certain pathological disorders.